The impact of the IFRS1 standards implementation on the quality of banks financial reporting: A survey of workers opinion in the private banks in Dohuk Governorate - Ali , Sherzad; Abdullah, Ali (Humanities Journal of University of Zakho, 2023)
The paper aims to highlight the developments in the field of accounting standards represented by the development of International Financial Reporting Standards (IFRS1). The research also attempts to identify the importance and effect of International Financial Reporting Standards (IFRS1) application on the quality of financial reporting in banks working in Dohuk Governorate. In addition, it demonstrates the impact of (IFRS1) on the objectives and the components of financial statements of these banks. The significance of this paper is to address one of the important and recent topics in the area of international standards, namely standard (IFRS1) and the level of their impact on the quality of financial reporting. The research reached number of conclusions, the most important one: the research illustrated through statistical analysis the possibility of applying international financial reporting standards (IFRS1) in these banks. The application of financial reporting standards will contribute to improving the quality of financial reports so as to reflect the economic reality of the banks under investigation. The study recommended that these banks have to apply international financial reporting standards as they have a positive impact on the quality of financial reporting and its reflection on the decisions of investors.